IMPLEMENTING HEALTH IN ALL POLICIES IN RILEY COUNTY, KANSAS - Brunkow, Cheyenne (My University, 2022)
Determinants of health go beyond the direct choices people make. The environment people live in, access to healthy and affordable food, and safe transportation are just some of the factors that influence the health of a community. Local governments influence health and health equity through city planning, and local policy may influence regional policy via vertical diffusion. Health in All Policies is a sizeable intersectoral program to improve health through attention to the full range of social determinants. It challenges political and public service leaders to branch out of their usual roles and commits to reaching health goals. Health in All Policies can increase awareness of social determinants of health in non-health departments and encourage policymakers to include health as a priority when making decisions. The scope of the work was to give presentations to decision-makers in Riley County, including school boards, city and county commissioners, local advisory boards, and others, on Health in All Policies. The presentations took place March 2021 – February 2022. Success depends on the community's needs, and no program is one size fits all. Long-term, Health in All Policies implementation can bring light to non-health sectors and help improve the community's health. Health in All Policies aims to improve determinants of health and reduce inequities by designing policies with health uppermost in mind. Intersectoral work can achieve this with the common goal of a healthy community. Health is affected by a cascade of events, and Health in All Policies hopes to help close those gaps. Social determinants of health mainly influence population health and equity. Still, for Health in All Policies to be successful, there must be a shift in health policy from illness-oriented health care to social environments of daily living. The Center for Disease Control and Prevention uses this approach to help achieve both National Prevention Strategy and Healthy People goals [1]. Health in All Policies is diverse in that it can involve engagements from all levels of government and has been increasing in popularity. Successful implementation of Health in All Policies depends on intersectoral efforts, often with the public health sector taking the lead role. Current structural and political factors often prevent long-range strategies to improve the health of communities.
Keywords: Health in All Policies; Riley County; health equity; social determinants of health; public health